Text on back. Fieldmarshal Montgomery (on the right) is welcomed by Sir I. Kirkpatrick the British High Commissioner in Germany at Cologne-airport
Text on back. Fieldmarshal Montgomery (on the right) is welcomed by Sir I. Kirkpatrick the British High Commissioner in Germany at Cologne-airport.